Development of a composite lean index to measure lean implementation in Philippine manufacturing companies - Zalatar, Willy F. (Animo Repository, 2018)
Lean manufacturing has been gaining worldwide popularity as a means of reducing waste, improving quality, and increasing the competitiveness of manufacturing firms. This paper aims to develop a composite lean index (CLI) which can be used to measure the degree of lean adoption in Philippine manufacturing companies. The lean index employs actual quantitative data, rather than subjective assessment, which is more prevalent in the literature. Fifteen performance indicators divided into process and equipment, manufacturing planning and control, human resources, and supplier and customer relationships are proposed and then validated using empirical data. Results showed that a CLI, which yields a single value from 0 to 1, can be computed from the 15 metrics formulated using multi-attribute value theory. Manufacturing companies can utilize this index for monitoring progress of lean implementation through the years as well as for benchmarking purposes with other firms. On the other hand, academicians can benefit from this index since most statistical analyses in researches require numerical values as inputs. © 2018 by De La Salle University.